Flood flow study of Cimanuk River, Java, Indonesia - Putuhena, William Marcus; Tawatchai Tingsanchali; Suphat Vongvisessomjai; Preecha Kamronrithisorn; United Nations Development Programme (UNDP ) (Bangkok : Asian Institute of Technology, 1989)
Two types of flood flow models have been studied. The first is the one-dimensional flood flow model which is applied to simulate flood flow condition along the Cimanuk river. The second one is the two-dimensional flood flow model for simulating the propagation of flood wave due to the sudden break of the river dike onto Kertasemaya flood-prone area. In the river, the flood flow can be considered as one-dimensional. The basic equation s of the 1-D model are the continuity and momentum of the Saint Venant type. In the flood prone area the unsteady flow resulting from breaking of the dike is approximately two-dimensional in plan. The 2-D mathematical model is consisted of the equation of continuity and the X- and Y- momentum equations. The governing equations are derived based on the assumption of gradually varied flow which may be subjected to errors when applying to rapidly varied flow such that due to the breaking of dike. The correction coefficients have been applied to the water surface slope terms of the momentum equations in the 2-D model to correct these errors. The one-dimensional model has been calibrated and verified with the field data successfully. For the two-dimensional model no calibration is made due to lack of data. The results of the study show that the existing river dike can handle the 100-year flood without overtopping. A qualitative estimation of the spreading of flood wave in the flood plain due to an assumed breaking of dike is obtained from the 2-D model. Sensitivity analysis shows that the Manning roughness coefficient of both 1-D and 2-D models and the correction factors of the 2-D model have considerable effects on the computed results.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1989
Keywords: Hydraulics; Floods -- Indonesia -- Cimanuk River